Secondary School Students' Knowledge and Views on Laboratory Safety - Belkız Caymaz (Universitas Pendidikan Indonesia, 2021)
Laboratory studies are very important for science education but also involve various risks. It is possible to minimize these risks by providing a safe working environment. This study aims to determine the knowledge and views of secondary school students on laboratory safety and to identify their deficiencies in this regard. The survey method was used in the study. The study sample consists of 136 students from 6th, 7th, and 8th-grade students of a public secondary school in Kastamonu Province, Turkey. An open-ended questionnaire was used to determine the students' knowledge and views on the subject, and the data obtained were analyzed by the content analysis method. As a result of the study, it was seen that although secondary school students have some general information about laboratory safety, they have deficiencies in terms of most of the information. It was determined that students do not know most of the behaviors that must/must not be made in the laboratory, and they are not aware of some of the safety symbols in the science textbooks. In addition, most of the students stated that they don't feel competent about laboratory safety and need training on this subject.